A NUTRITIONAL STUDY OF TRIBAL AND NON-TRIBAL CHILDREN IN THE UDAIPUR REGION - TRIPATHI, NISHA; JAIN, SUMAN; SOGANI, SONAL; BHATNAGAR, SANDEEP; BHATNAGAR, MANI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: There is an evidence that nutrition has a significant impact on children’s development, adult health, and senescence. It is also known to have an impact on one’s physical and mental faculties. Malnutrition is now understood to be the root cause of a significant variety of health issues. To compare the nutritional condition of 300 (tribal and nontribal) children living in the Udaipur region, a dietary survey was conducted. Methods: In the present study, 300 tribal and non-tribal children between the ages of 1 and 12 were chosen for a dietary survey to evaluate their nutritional status. The survey was conducted using a questionnaire. Results and Conclusion: The statistics between tribal and non-tribal children showed that calorie, protein, fat, and carbohydrate intake was lower in the tribal children. When we compared the data between tribal and non-tribal children, we found that the non-tribal children’s calorie, protein, fat, and carbohydrate intake was not superior. Ascorbic acid and B-carotene intake among non-tribals is also less than that advised by the ICMR and is approximately twice as low as that among their tribal counterparts. The statistics on tribal and non-tribal children made it abundantly evident that nutritional intake is low that consumption of fat among dense nutrients is significantly lower and that intake of antioxidant nutrients such as ascorbic acid and beta-carotene is similarly poor.